COLLABORATIVE PROBLEM-SOLVING PROCESS IN JUNIOR HIGH SCHOOL STUDENT ASSOCIATION MATERIALS BASED ON HETEROGENEITY OF MATHEMATICAL ABILITY - Erna Wati; Rooselyna Ekawati; Agung Lukito (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Students' mathematical problem-solving skills currently demonstrate a low proficiency, thus necessitating a collaborative approach that effectively integrates cognitive and social abilities in problem resolution. This study aims to describe the process of Collaborative Problem Solving (CPS) among students at SMPN 22 Surabaya on the topic of sets, based on the heterogeneity of their mathematical ability, namely the high-medium, high-low, and medium-low groups. The research employed a descriptive qualitative approach, utilizing problem-solving tests, video interaction observations, and semi-structured interviews. The data were analyzed using established CPS indicators and standard problem-solving steps. The findings reveal that the high-medium group successfully executed a complete CPS process characterized by balanced interaction. In contrast, the high-low group exhibited unequal collaboration, marked by the dominance of the high-ability student. Furthermore, the medium-low group experienced significant obstacles in nearly all problem-solving stages and was heavily dependent on researcher assistance. The study concludes that the range of mathematical ability within a group is a determining factor for the success of CPS, as ability gaps impede the necessary exchange of ideas, negotiation of meaning, and joint strategy formulation. The practical implications of this research underscore the importance of mapping student capabilities and reinforcing fundamental concepts prior to implementing CPS in mathematics instruction.